Lithium supplement material, electrode plate and battery
By using conductive substrates and lithium-containing substrates embedded in conductive substrates in lithium-ion batteries, combining carbon fibers and graphite fibers to optimize the electrode sheet structure, the problems of poor safety and effectiveness of lithium-ion batteries are solved, and the battery is realized Resistance reduction and cycle performance improvement.
Patent Information
- Application Number
- CN202411617314.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-17
AI Technical Summary
The lithium supplement substances of existing lithium-ion batteries have high chemical activity and poor safety, which can easily lead to an increase in battery expansion rate and internal resistance, and poor lithium supplementation effect, making it difficult to improve both the lithium supplement effect and safety performance.
Using conductive substrates and lithium-containing substrates embedded in conductive substrates to form a conductive network, combine carbon fibers and graphite fibers to control their size and distribution, form lithium embedded areas and non-lithium embedded areas, and optimize the electrode sheet structure to improve lithium supplementation effect and safety sex.
Effectively reduce battery internal resistance, improve battery cycle life and circulation performance, take into account high lithium supplement effect and safety performance, alleviate the expansion of negative electrode active material, and accommodate more electrolyte.
Smart Images

Figure CN119324263A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium supplement material, an electrode sheet and a battery. Background Art
[0002] With the advent of the 5G era and the large-scale use of electric vehicles, higher requirements are placed on the cycle life of lithium-ion batteries. The storage and release of lithium-ion battery capacity is based on Li + The reversible embedding and extraction in the electrode material will form a solid electrolyte interface SEI film and CEI film on the surface of the active material particles during the first charge and discharge process of the battery. The SEI film will continuously and irreversibly consume the active lithium from the positive electrode sheet. The formation of the CEI film will also consume the active lithium, which is not conducive to the long-term cycle performance of the battery and the first coulombic efficiency of the battery will also be reduced.
[0003] At present, most of the pre-lithiation technology is used to compensate for the irreversible loss of active lithium to ensure sufficient active lithium in the battery. Specifically, it can be to add a lithium source to the positive or negative electrode before activating the battery. The commonly used lithium replenishment method is to add metal lithium powder to the electrode sheet or roll metal lithium foil, lithium belt and other lithium replenishment materials on the surface of the electrode sheet. However, this method of directly generating lithium replenishment materials on the electrode sheet will seriously reduce the interface performance of the battery and is more likely to form high resistance. Moreover, the above-mentioned lithium replenishment materials have high chemical activity and poor safety, which can easily lead to an increase in the battery expansion rate, and the lithium replenishment effect is not good, and the improvement of the first effect and cycle performance is limited.
[0004] Therefore, how to improve the lithium replenishment effect and safety performance while reducing the internal resistance of the battery is a technical problem that needs to be solved urgently in this field. Summary of the invention
[0005] The present invention provides a lithium supplement material, which is used to solve the problems in the prior art that the lithium supplement material has high chemical activity, poor safety, and is likely to cause an increase in battery expansion rate, an increase in internal resistance, and a poor lithium supplement effect.
[0006] The present invention provides an electrode sheet and a battery, comprising the above-mentioned lithium supplement material, which can have both high lithium supplement effect and safety performance, and can also reduce internal resistance and improve battery performance.
[0007] The present invention provides a lithium supplement material, which includes a conductive matrix and a lithium-containing matrix embedded in at least a portion of the conductive matrix;
[0008] The conductive matrix includes carbon fibers and / or graphite fibers;
[0009] The chemical formula of the lithium-containing matrix is Li x C6, where 0.2≤x≤0.7;
[0010] The carbon fiber and / or the graphite fiber has a diameter of 2 to 500 nm and a length of 1 to 20 μm.
[0011] Furthermore, the lithium supplement material includes a lithium insertion region and a non-lithium insertion region, and the lithium supplement material satisfies: 20%≤A1 / (A1+A2)×100%≤70%, wherein A1 is the area of the lithium insertion region, and A2 is the area of the non-lithium insertion region.
[0012] The present invention further provides an electrode sheet, comprising a current collector and a functional layer disposed on at least a portion of the surface of the current collector, wherein the functional layer comprises the above-mentioned lithium supplement material.
[0013] Further, the functional layer comprises a lithium supplement layer and an active material layer which are stacked, the lithium supplement layer comprises the lithium supplement material, and the active material layer comprises the active material; or,
[0014] The functional layer includes a mixed layer, and the mixed layer includes an active material and the lithium supplement material; or,
[0015] The functional layer includes an active material layer and a mixed layer which are stacked, the active material layer includes an active material, and the mixed layer includes an active material and the lithium supplementing material.
[0016] Further, the electrode sheet is a positive electrode sheet, in which the active material layer is a positive electrode active material layer, and the active material is a positive electrode active material; or, the electrode sheet is a negative electrode sheet, in which the active material layer is a negative electrode active material layer, and the active material is a negative electrode active material;
[0017] Wherein, the active material layer and the lithium supplement layer are sequentially arranged on the two surfaces of the current collector respectively; or,
[0018] The lithium replenishing layer and the active material layer are sequentially arranged on two surfaces of the current collector respectively; or,
[0019] The active material layer includes a first active material layer and a second active material layer, and the first active material layer, the lithium replenishing layer and the second active material layer are sequentially arranged on two surfaces of the current collector respectively; or,
[0020] The active material layer is disposed on any one surface of the current collector, and the active material layer and the lithium supplement layer are sequentially disposed on the other surface; or,
[0021] The active material layer is disposed on any one surface of the current collector, and the lithium replenishing layer and the active material layer are sequentially disposed on the other surface; or,
[0022] The mixed layer is disposed on both surfaces of the current collector; or,
[0023] The mixed layer and the active material layer are sequentially disposed on both surfaces of the current collector; or,
[0024] The active material layer and the mixed layer are sequentially disposed on both surfaces of the current collector.
[0025] Furthermore, in the negative electrode sheet, the negative electrode active material includes a silicon-based material, and the mass percentage of the silicon-based material in the negative electrode active material layer is 0 to 50%; or,
[0026] In the positive electrode sheet, the positive electrode active material includes a metal oxide represented by Formula 1 and / or Formula 2;
[0027] Li a1 Co x1 A 1 k1 O2 Formula 1
[0028] Li a2 Ni x2 Co y2 D z2 A 2 k2 O2 Formula 2
[0029] Where, 0.85≤al≤1.1, 0.85≤a2≤1.1, 0.3≤x1≤0.9, 0.3 <x2≤0.9,0≤y2≤0.5,0.1≤z2≤0.5,0≤kl≤0.15,0≤k2≤0.15;
[0030] D includes at least one of Mn or Al;
[0031] A 1 and A 2 Each independently includes at least one of Al, Mg, Ti, Zr, Y, La, W, B, Nb and Mn.
[0032] Furthermore, in the mixed layer, the mass ratio of the lithium supplement material to the active material is (5-10):(90-95).
[0033] Furthermore, the porosity of the lithium supplement layer satisfies Formula 3:
[0034] ε1=(0.4~1)ε2 Formula 3
[0035] In Formula 3, ε1 is the porosity of the lithium supplement layer, in %, and ε2 is the porosity of the active material layer, in %.
[0036] Furthermore, the porosity ε1 of the lithium supplement layer is 16-35%, and / or the porosity ε2 of the active material layer is 20-45%.
[0037] Furthermore, the electrode sheet is a negative electrode sheet, and the lithium supplement layer further comprises a binder and a conductive agent; wherein the mass ratio of the lithium supplement material, the binder and the conductive agent is (80-98): (1-10): (1-10);
[0038] Or, the electrode sheet is a positive electrode sheet, and the lithium supplement layer further includes an inorganic substance and a conductive agent; wherein the mass ratio of the lithium supplement material, the inorganic substance and the conductive agent is (10-40): (55-90): (0-5);
[0039] Preferably, the conductive agent includes at least one of conductive carbon black, conductive graphite, carbon fiber, carbon nanotube, and graphene;
[0040] Preferably, the inorganic substance includes at least one of boehmite, alumina, silicon dioxide and lithium iron phosphate.
[0041] The present invention also provides a battery, comprising any one of the lithium supplement materials described above or any one of the electrode sheets described above.
[0042] The lithium supplement material provided by the present invention includes a conductive matrix and a lithium-containing matrix embedded in at least part of the conductive matrix. The conductive matrix has good conductivity and is easy to form a good conductive network in the electrode, which can reduce electrode polarization, reduce battery internal resistance and improve battery performance; and the lithium supplement material can alleviate the expansion of the negative electrode active material. When lithium ions are consumed, a thickness space is reserved to alleviate the expansion of the negative electrode sheet; and the lithium supplement material can accommodate more electrolyte, thereby improving the battery cycle life and cycle performance; at the same time, the diameter of the conductive matrix carbon fiber and / or graphite fiber is controlled to be 2 to 500nm and the length is 1 to 20μm, which can make the conductive matrix have strong toughness, and further form a network structure, increase the toughness of the electrode sheet and improve the strength of the electrode. In summary, the lithium supplement material provided by the present invention can take into account both the improvement of lithium supplement effect and safety performance, and can reduce the internal resistance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 Schematic diagram of the cross-sectional structure of an electrode sheet in one embodiment of the present invention;
[0044] Figure 2 Schematic diagram of the cross-sectional structure of an electrode sheet in one embodiment of the present invention;
[0045] Figure 3 Schematic diagram of the cross-sectional structure of an electrode sheet in one embodiment of the present invention;
[0046] Figure 4Schematic diagram of the cross-sectional structure of an electrode sheet in one embodiment of the present invention;
[0047] Figure 5 Schematic diagram of the cross-sectional structure of an electrode sheet in one embodiment of the present invention;
[0048] Figure 6 Schematic diagram of the cross-sectional structure of an electrode sheet in one embodiment of the present invention;
[0049] Figure 7 Schematic diagram of the cross-sectional structure of an electrode sheet in one embodiment of the present invention;
[0050] Figure 8 Schematic diagram of the cross-sectional structure of an electrode sheet in one embodiment of the present invention.
[0051] Description of reference numerals:
[0052] 1-current collector;
[0053] 2-active material layer;
[0054] 21- first active material layer;
[0055] 22- second active material layer;
[0056] 3-lithium replenishment layer;
[0057] 4- Mixed layer. DETAILED DESCRIPTION
[0058] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0059] In a first aspect, the present invention provides a lithium supplement material, the lithium supplement material comprising a conductive matrix and a lithium-containing matrix embedded in at least a portion of the conductive matrix;
[0060] The conductive matrix includes carbon fibers and / or graphite fibers;
[0061] The chemical formula of the lithium-containing matrix is Li x C6, where 0.2≤x≤0.7;
[0062] The diameter of the carbon fiber and / or graphite fiber is 2 to 500 nm, and the length is 1 to 20 μm.
[0063] The lithium supplement material provided by the present invention comprises a conductive matrix and a lithium-containing matrix embedded in at least a part of the conductive matrix; the conductive matrix comprises carbon fibers and / or graphite fibers.
[0064] The lithium-supplementing material includes a conductive matrix and a lithium-containing matrix embedded in at least a portion of the conductive matrix, wherein the chemical formula of the lithium-containing matrix is Li x C6, the inventors found that when 0.2≤x≤0.7, the lithium replenishment amount of the lithium-containing matrix can be further increased, the lithium replenishment effect can be better achieved, and the conductivity of the lithium replenishment material can be further improved, the interface performance of the battery can be improved, and the internal resistance of the battery can be reduced without the need to add additional conductive agents.
[0065] The conductive matrix has good conductivity, and after the lithium-containing matrix is embedded in part of the conductive matrix, the formed lithium-supplementing material can form a good conductive network in the electrode, effectively reducing electrode polarization and lowering the internal resistance of the battery.
[0066] When the active lithium in the positive and negative electrodes is consumed during the first charge and discharge process of the battery, the lithium supplement material provided by the present invention can be used as an active lithium source to make up for the active lithium consumption of the positive and negative electrodes during the first charge and discharge of the battery, and ensure the demand for active lithium during the cycle process; in addition, when the active lithium in the lithium supplement material is consumed, thickness space can be reserved to alleviate the expansion of the negative electrode sheet, and more electrolyte can be accommodated, thereby improving the cycle life and cycle performance of the battery.
[0067] By further controlling the size of the conductive matrix carbon fiber and / or graphite fiber to have a larger aspect ratio, that is, the diameter of the conductive matrix is 2 to 500 nm and the length is 1 to 20 μm, the conductive matrix can further form a network structure with stronger toughness, better alleviate the expansion of the negative electrode active material, and further increase the toughness of the pole piece, improve the strength of the electrode and the cycle performance.
[0068] The lithium supplement material provided by the present invention includes a conductive matrix and lithium ions embedded in at least part of the conductive matrix. The conductive matrix has good conductivity and is easy to form a good conductive network in the electrode, which can reduce electrode polarization, reduce battery internal resistance and improve battery performance; and the lithium supplement material can alleviate the expansion of the negative electrode active material. When the lithium ions are consumed, the thickness space is reserved to alleviate the expansion of the negative electrode sheet; and the lithium supplement material can accommodate more electrolyte, thereby improving the battery cycle life and cycle performance; in addition, the size of the conductive matrix has a large aspect ratio, which can not only enable the conductive matrix to further form a network structure, but also has strong toughness, which can better alleviate the volume expansion of the negative electrode active material, and further increase the toughness of the electrode sheet, improve the strength of the electrode, and improve the cycle performance of the battery. In summary, the lithium supplement material provided by the present invention can have both high lithium supplement effect and safety performance, and can reduce the internal resistance of the battery.
[0069] The present invention does not limit the specific source of the lithium supplement material, which can be obtained from the market or prepared by the following method:
[0070] (1) Taking a conductive matrix material of any size, ultrasonically cleaning the conductive matrix material with ethanol, acetone, and pure water to remove impurities; after cleaning, drying and baking in a baking oven at 60° C. to 80° C. for 24 to 48 hours for use;
[0071] (2) A lithium foil not smaller than the size of the conductive matrix raw material is placed in an aluminum shell or an aluminum composite foil shell, and the spare conductive matrix is closely attached to the lithium foil. Then, in a dry environment, 0.8-2 mol / L of electrolyte is injected into the closely attached lithium foil and the conductive matrix, so that the electrolyte completely infiltrates the conductive matrix raw material; after injecting the electrolyte, the outer aluminum shell or aluminum composite foil shell is sealed and pre-lithiation treatment is performed for a treatment time of 10-360 min (i.e., the lithium foil is used as the anode and the conductive matrix is used as the cathode, and charging is performed for a charging time of 10-360 min). After the treatment is completed, the conductive matrix and the lithium foil are peeled off, and the conductive matrix is cleaned with dimethyl carbonate (DMC) for 2-4 times, and dried at 25±5°C to obtain a pre-lithiation conductive matrix, i.e., a lithium supplement material.
[0072] Among them, the conductive matrix raw material includes carbon fiber and / or graphite fiber, and the carbon fiber includes carbon fiber paper and / or carbon fiber cloth; the matrix fiber of the conductive matrix raw material (referring to the raw material for making carbon fiber and / or graphite fiber) can be viscose fiber belonging to hard carbon, intermediate phase asphalt-based carbon fiber belonging to soft carbon, or polyacrylonitrile-based carbon fiber between the two.
[0073] The lithium salt in the electrolyte includes lithium bis(trifluoromethanesulfonyl)imide (LiTFSi) and / or lithium hexafluorophosphate (LiPF6).
[0074] It can be understood that in step (2), due to the low electrochemical reduction potential of Li metal, in the presence of the electrolyte, the lithium metal in the lithium foil and the conductive matrix raw material in direct physical contact will spontaneously discharge under the drive of the potential difference to form a lithium-containing matrix embedded in the conductive matrix, with the chemical formula Li x C6 (0.2≤x≤0.7), obtain lithium supplement material.
[0075] Furthermore, when the lithium-supplementing material is made into an electrode sheet, the prepared lithium-supplementing material needs to be further processed. For example, the lithium-supplementing material is mechanically crushed to better mix with other required raw materials in the electrode sheet. It should be noted that mechanical crushing can only destroy its macroscopic structure but not its microscopic structure.
[0076] In a specific embodiment, the lithium supplement material includes a lithium insertion region and a non-lithium insertion region, and the lithium supplement material satisfies: 20%≤A1 / (A1+A2)×100%≤70%, wherein A1 is the area of the lithium insertion region, and A2 is the area of the non-lithium insertion region.
[0077] It should be noted that the above-mentioned lithium-embedded region refers to the region where the lithium-containing matrix Li is embedded in the conductive matrix. x The region of C6 (0.2≤x≤0.7).
[0078] It is understandable that the surface of the lithium supplement material will have rough and cracked areas. The inventors have found that when the lithium insertion area and the non-lithium insertion area in the lithium supplement material provided by the present invention satisfy the above relationship, the lithium supplement effect can be further improved, and at the same time, the internal resistance can be reduced and the performance of the battery can be improved.
[0079] The “lithium insertion region area A1” and the “non-lithium insertion region area A2” in the present invention can be obtained by SEM testing.
[0080] In a second aspect, the present invention provides an electrode sheet, comprising a current collector and a functional layer disposed on at least a portion of the surface of the current collector, wherein the functional layer comprises the lithium supplement material of the first aspect.
[0081] The present invention does not limit the electrical properties of the electrode, which can be a negative electrode or a positive electrode.
[0082] The present invention also does not limit the application scope of the electrode sheet, and it can be used for wound battery cells, stacked battery cells, special-shaped battery cells, and directly used as an electrode sheet of a flexible battery.
[0083] The surface of the current collector refers to the outermost surface in the length direction and the width direction of the current collector, that is, the largest and opposite front and back surfaces among the six surfaces of the current collector.
[0084] The present invention does not limit the specific type of current collector; optionally, the positive electrode current collector includes any one of aluminum foil, aluminum foil containing through holes, aluminum foil containing concave-convex structure, and composite aluminum foil; the negative electrode current collector in the negative electrode sheet includes at least one of copper foil, foam copper, composite copper foil and composite current collector.
[0085] When the electrode sheet provided by the present invention is a positive electrode sheet, the lithium supplement material in the functional layer of the positive electrode sheet can not only have a lithium supplement effect, but also release the expansion of the negative electrode, increase the amount of additional electrolyte and increase the charge conduction capacity of the positive electrode material, reduce the internal resistance of the battery, and improve the performance of the battery.
[0086] When the electrode sheet provided by the present invention is a negative electrode sheet, on the one hand, the lithium-replenishing material in the functional layer of the negative electrode sheet can be used as an active lithium ion source to supplement the consumption of active lithium in the positive and negative electrodes during the initial charge and discharge process of the battery, and at the same time can ensure the demand for active lithium in the cycle process; on the other hand, the lithium-replenishing material can release a part of the thickness space after replenishing lithium ions, and can release the expansion caused by the negative electrode, providing a buffer area for the expansion; on the other hand, the lithium-replenishing material can increase the additional liquid storage volume in the later stage of the cycle to ensure sufficient electrolyte in the later stage of the cycle; finally, the size of the conductive matrix has a large aspect ratio, which can not only further form a network structure, but also has strong toughness, better alleviate the volume expansion, and make the electrode sheet have higher toughness, strength and cycle performance; at the same time, the conductive matrix in the lithium-replenishing material has good conductivity, which can reduce the internal resistance of the battery and improve the battery performance.
[0087] In a specific embodiment, the functional layer includes a lithium replenishing layer and an active material layer which are stacked, the lithium replenishing layer includes a lithium replenishing material, and the active material layer includes an active material; or,
[0088] The functional layer includes a mixed layer, and the mixed layer includes an active material and a lithium supplement material; or,
[0089] The functional layer includes an active material layer and a mixed layer which are stacked, the active material layer includes an active material, and the mixed layer includes an active material and a lithium supplementing material.
[0090] The present invention does not impose any special limitation on the total number of lithium replenishing layers and active material layers. The lithium replenishing layers are preferably 1 to 2 layers, and the active material layers are preferably 1 to 2 layers.
[0091] It should be noted that the stacking method of the lithium replenishing layer and the active material layer can be AB, BA, ABA, BAB, etc., wherein A is the lithium replenishing layer and B is the active material layer.
[0092] The present invention does not limit the specific arrangement of the functional layer in the electrode sheet. The functional layer can be arranged symmetrically on both the front and back surfaces of the current collector, or can be arranged unilaterally on any surface of the current collector.
[0093] In a specific embodiment, the electrode sheet is a positive electrode sheet, in which the active material layer is a positive electrode active material layer, and the active material is a positive electrode active material;
[0094] Alternatively, the electrode sheet is a negative electrode sheet, in which the active material layer is a negative electrode active material layer, and the active material is a negative electrode active material.
[0095] Specifically, in one embodiment, an active material layer and a lithium replenishing layer are sequentially disposed on both surfaces of the current collector. Figure 1 is a schematic diagram of the cross-sectional structure of an electrode sheet in one embodiment, Figure 1In the embodiment, active material layers 2 are respectively arranged on two surfaces of the current collector 1 , and a lithium supplement layer 3 is arranged on the outer surface of the active material layer 2 .
[0096] In one embodiment, a lithium supplement layer and an active material layer are sequentially disposed on both surfaces of the current collector. Figure 2 is a schematic diagram of the cross-sectional structure of an electrode sheet in one embodiment, Figure 2 In the embodiment, two surfaces of the current collector 1 are respectively provided with lithium replenishing layers 3 , and the outer surface of the lithium replenishing layer 3 is provided with an active material layer 2 .
[0097] In one embodiment, the active material layer includes a first active material layer and a second active material layer, and the first active material layer, the lithium replenishing layer and the second active material layer are sequentially disposed on both surfaces of the current collector. Figure 3 is a schematic diagram of the cross-sectional structure of an electrode sheet in one embodiment, Figure 3 In the embodiment, the first active material layer 21 is disposed on both surfaces of the current collector 1 , the lithium replenishing layer 3 is disposed on both outer surfaces of the first active material layer 21 , and the second active material layer 22 is disposed on both outer surfaces of the lithium replenishing layer 3 .
[0098] In one embodiment, an active material layer is disposed on any one surface of the current collector, and an active material layer and a lithium supplement layer are sequentially disposed on the other surface. Figure 4 is a schematic diagram of the cross-sectional structure of an electrode sheet in one embodiment, Figure 4 In the embodiment, active material layers 2 are arranged on both surfaces of a current collector 1 , and a lithium supplementing layer 3 is arranged on the outer surface of one of the active material layers 2 .
[0099] In one embodiment, an active material layer is disposed on any one surface of the current collector, and a lithium supplement layer and an active material layer are sequentially disposed on the other surface. Figure 5 is a schematic diagram of the cross-sectional structure of an electrode sheet in one embodiment, Figure 5 In the embodiment, a lithium supplement layer 3 is provided on one surface of the current collector 1 , an active material layer 2 is provided on the other surface, and an active material layer 2 is provided on the outer surface of the lithium supplement layer 3 .
[0100] In one embodiment, mixed layers are respectively disposed on both surfaces of the current collector. Figure 6 is a schematic diagram of the cross-sectional structure of an electrode sheet in one embodiment, Figure 6 In the embodiment, the mixed layer 4 is arranged on both surfaces of the current collector 1 .
[0101] In one embodiment, a mixed layer and an active material layer are sequentially disposed on both surfaces of the current collector. Figure 7 is a schematic diagram of the cross-sectional structure of an electrode sheet in one embodiment, Figure 7In the embodiment, mixed layers 4 are respectively arranged on both surfaces of the current collector 1 , and an active material layer 2 is arranged on the outer surface of the mixed layer 4 .
[0102] In one embodiment, an active material layer and a mixed layer are sequentially disposed on both surfaces of the current collector. Figure 8 is a schematic diagram of the cross-sectional structure of an electrode sheet in one embodiment, Figure 8 In the embodiment, active material layers 2 are respectively arranged on both surfaces of the current collector 1 , and a mixed layer 4 is arranged on the outer surface of the active material layer 2 .
[0103] Furthermore, when the functional layer includes a stacked lithium replenishing layer 3 and an active material layer 2, and the lithium replenishing layer is directly connected to at least a portion of the surface of the current collector 1, the lithium replenishing layer also includes a conductive agent, and the mass ratio of the conductive agent to the lithium replenishing material is 1: (10-30).
[0104] In a specific embodiment, in the negative electrode sheet, the negative electrode active material includes a silicon-based material, and the mass percentage of the silicon-based material in the negative electrode active material layer is 0 to 50%.
[0105] It should be noted that when the negative electrode active material layer is multi-layered, the mass content of the silicon-based material in each negative electrode active material layer is 0 to 50%.
[0106] Preferably, the silicon-based material in the present invention includes at least one of elemental silicon, silicon-carbon material, silicon-oxygen material and silicon alloy.
[0107] The inventors found that when the electrode sheet is used as a negative electrode sheet, the energy density and specific capacity of the battery can be improved by increasing the mass percentage of the silicon-based material in each active layer and controlling the mass percentage of the silicon-based material in each active layer to 0-50%.
[0108] In a specific embodiment, in the positive electrode sheet, the positive electrode active material includes a metal oxide represented by Formula 1 and / or Formula 2;
[0109] Li a1 Co x1 A 1 k1 O2 Formula 1
[0110] Li a2 Ni x2 Co y2 D z2 A 2 k2 O2 Formula 2
[0111] Where, 0.85≤al≤1.1, 0.85≤a2≤1.1, 0.3≤x1≤0.9, 0.3 <x2≤0.9,0≤y2≤0.5,0.1≤z2≤0.5,0≤kl≤0.15,0≤k2≤0.15;
[0112] D includes at least one of Mn or Al;
[0113] A 1 and A 2 Each independently includes at least one of Al, Mg, Ti, Zr, Y, La, W, B, Nb and Mn.
[0114] It should be noted that when the positive electrode active material layer is multi-layered, each positive electrode active material layer includes the positive electrode active material represented by Formula 1 and / or Formula 2.
[0115] It can be understood that the cost of the positive electrode active material shown in Formula 2 is relatively low. By using the positive electrode active material shown in Formula 1 and the positive electrode active material shown in Formula 2 at the same time, the material cost can be appropriately reduced, and the rate performance and energy density of the active layer, as well as the safety performance of the lithium-ion battery can be improved. For example, when the positive electrode active material shown in Formula 2 is a ternary material and the positive electrode active material shown in Formula 1 is lithium cobalt oxide, compared with the more expensive lithium cobalt oxide, the ternary material is cheap, and its cycle performance is excellent, and the gram capacity of the material is high. Therefore, by using two positive electrode active materials as positive electrode active materials at the same time, the cycle performance and gram capacity of the material can be improved while reducing the cost of the positive electrode active material, thereby improving the cycle capacity retention rate of the lithium-ion battery.
[0116] Furthermore, although the cost of the positive electrode active material shown in Formula 2 is relatively low, the processing performance, compaction density, and average platform voltage of the positive electrode active material shown in Formula 2 are slightly lower than those of the positive electrode active material shown in Formula 1. Therefore, the relative content of the positive electrode active material shown in Formula 1 should not be too low. In a preferred embodiment, the mass ratio of the positive electrode active material shown in Formula 1 to the positive electrode active material shown in Formula 2 is 1:99 to 99:1.
[0117] In a specific embodiment, in the mixed layer, the mass ratio of the lithium supplement material to the active material is (5-10):(90-95). When the lithium supplement material and the active material are both present in the mixed layer, by further limiting the mass ratio of the two, the conductive matrix in the lithium supplement material can form a better coating on the active material, further forming a conductive network, and is conducive to further reducing electrode expansion after the active material is embedded with lithium.
[0118] Furthermore, the mixed layer also includes a conductive agent, the D50 particle size of the lithium supplement material is ≤20μm, and the D50 particle size of the conductive agent is ≤15μm; the D50 particle size of the lithium supplement material is larger than the D50 particle size of the conductive agent. In this case, it is beneficial to form a better conductive network in the mixed layer, which is beneficial to further reduce electrode expansion after the active material is embedded with lithium.
[0119] The "D50 particle size" in the present invention refers to the particle size corresponding to when the cumulative volume distribution percentage of the particles reaches 50%.
[0120] In a specific embodiment, the electrode sheet is a positive electrode sheet, and the D50 particle size of the positive electrode active material is 3 to 15 μm.
[0121] In a specific embodiment, the electrode sheet is a negative electrode sheet, and the D50 of the negative electrode active material is 5 to 20 μm.
[0122] In a specific embodiment, the porosity of the lithium supplement layer satisfies Formula 3:
[0123] ε1=(0.4~1)ε2 Formula 3
[0124] In Formula 3, ε1 is the porosity of the lithium supplement layer, in %, and ε2 is the porosity of the active material layer, in %.
[0125] It should be noted that when the electrode sheet is a positive electrode sheet, ε1 is the porosity of the lithium replenishing layer in the positive electrode sheet, and ε2 is the porosity of the positive electrode active material layer; when the electrode sheet is a negative electrode sheet, ε1 is the porosity of the lithium replenishing layer in the negative electrode sheet, and ε2 is the porosity of the negative electrode active material layer.
[0126] It should be noted that when the electrode sheet contains multiple active material layers and / or multiple lithium replenishing layers, the above ε1 is the average porosity of the multiple active material layers, and ε2 is the average porosity of the multiple lithium replenishing layers.
[0127] It can be understood that due to the embedding and extraction of lithium ions, the porosity will change while causing the thickness change. By further limiting the relationship between the porosity of the active material layer and the porosity of the lithium replenishment layer, the increase in porosity of the positive electrode after lithium removal can be further compensated, the collapse of the positive electrode active material can be avoided, and the resistance can be reduced, so as to further improve the electrolyte storage capacity of the lithium replenishment layer in the negative electrode sheet; and the expansion of the negative electrode can be further alleviated, the cycle life can be improved, and the diffusion rate of lithium ions can be increased.
[0128] In a specific embodiment, the porosity ε1 of the lithium supplement layer is 16-35%. Within this range, the expansion of the negative electrode can be further alleviated and the cycle life of the battery can be improved.
[0129] Exemplarily, the porosity ε1 is 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34% or 35%.
[0130] In a specific embodiment, the porosity ε2 of the active material layer is 20-45%. Within this range, the collapse of the negative electrode structure can be further avoided and the resistance can be reduced. At the same time, the liquid storage capacity of the lithium replenishment layer in the electrode can be increased, the expansion of the negative electrode can be further alleviated, and the cycle life of the battery can be extended.
[0131] Exemplarily, the porosity ε2 is 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44% or 45%.
[0132] In a specific embodiment, in the negative electrode sheet, the thickness of the lithium supplement layer satisfies Formula 4:
[0133] (D2-D) / D1=0.8~1 Formula 4
[0134] In formula 4, D is the thickness of the negative electrode active material layer, in μm; D1 is the thickness of the lithium supplement layer, in μm; and D2 is the thickness of the negative electrode active material layer without the lithium supplement layer after full charge, in μm.
[0135] In the present invention, the lithium ion battery including the electrode sheet of the present invention and the lithium ion battery including the electrode sheet without the lithium supplement layer differ only in whether the electrode sheet contains the lithium supplement layer, and the other aspects are completely the same.
[0136] Among them, D2 is measured within 50 cycles of charge and discharge of lithium-ion batteries.
[0137] It should be noted that when the negative electrode sheet contains multiple layers of negative electrode active material layers and / or multiple layers of lithium replenishing layers, the above-mentioned D is the average thickness of the multiple layers of negative electrode active material layers, D1 is the average thickness of the multiple layers of lithium replenishing layers, and D2 is the average thickness of the multiple layers of negative electrode active material layers without lithium replenishing layers.
[0138] The lithium replenishing layer provided by the present invention can release a part of the thickness space after replenishing lithium ions, provide a buffer area for the expansion of the negative electrode, and compensate for the impact of the expansion of the negative electrode; therefore, by limiting the relationship between the thickness change of the negative electrode active material layer in the negative electrode sheet during the charge and discharge process and the thickness of the lithium replenishing layer, the above functions can be better achieved, the expansion of the negative electrode can be further alleviated, and the cycle life can be improved; and the loss of active materials in the active layer can be further reduced, the interface problem can be improved, and the side reactions can be reduced.
[0139] Further, the thickness of the lithium supplement layer in the negative electrode sheet is 0.5-10 μm. Exemplarily, the thickness of the lithium supplement layer is 0.5 μm, 2 μm, 4 μm, 5 μm, 6 μm, 8 μm or 10 μm.
[0140] In a specific embodiment, the electrode sheet is a negative electrode sheet, and the lithium replenishing layer further includes a binder and a conductive agent; wherein the mass ratio of the lithium replenishing material, the binder and the conductive agent is (80-98): (1-10): (1-10).
[0141] It can be understood that when the electrode sheet is a negative electrode sheet, a binder and a conductive agent are also required in the lithium replenishing layer. By further limiting the mass ratio of the lithium replenishing material, the binder and the conductive agent, the adhesion between the lithium replenishing layer and the current collector or active material layer can be better enhanced, and the amount of lithium replenishment can be further increased.
[0142] In a specific embodiment, the electrode sheet is a positive electrode sheet, and the lithium replenishing layer further includes an inorganic substance and a conductive agent; wherein the mass ratio of the lithium replenishing material, the inorganic substance and the conductive agent is (10-40): (55-90): (0-5).
[0143] It can be understood that when the electrode sheet is a positive electrode sheet, the lithium replenishing layer also includes inorganic substances and conductive agents; the combination of inorganic substances in the lithium replenishing layer can improve the safety of the battery, and the addition of conductive agents can further improve the ion transmission efficiency and improve the conductivity of the electrode.
[0144] Preferably, the conductive agent includes at least one of conductive carbon black, conductive graphite, carbon fiber, carbon nanotube, and graphene.
[0145] Preferably, the inorganic substance includes at least one of boehmite, alumina, silicon dioxide, and lithium iron phosphate.
[0146] Preferably, the binder includes an aqueous binder and / or an oily binder; the oily binder is selected from at least one of polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polytetrafluoroethylene (PTEE), and polyvinylidene fluoride-hexafluoropropylene; the aqueous binder is selected from at least one of styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose (CMC-Na), polyacrylic acid (PAA), polyacrylonitrile (PAN), polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), sodium alginate, and β-cyclodextrin polymer (β-CDP).
[0147] It can be understood that during the preparation process, a solvent is also required in the lithium replenishing layer to mix the raw materials required in the lithium replenishing layer and prepare the lithium replenishing slurry. Preferably, the solid content of the lithium replenishing slurry is 65-85%, and the viscosity is 4000-12000 MPa·S; optionally, the solvent includes N-methyl-2-pyrrolidone (NMP).
[0148] The present invention does not limit the preparation method of the electrode sheet. Figure 1 For example, the electrode sheet can be prepared by the following method:
[0149] (1) mechanically crushing the lithium supplementing material to obtain a crushed lithium supplementing material;
[0150] (2) mixing all raw materials required for the lithium replenishing layer (including lithium replenishing material, binder and conductive agent) and stirring evenly to obtain lithium replenishing slurry;
[0151] Mixing and stirring all the raw materials required for the active material layer (including active material, binder and conductive agent) to obtain active slurry;
[0152] (3) The active slurry is evenly coated on the front and back surfaces of the current collector to obtain an active layer; the lithium supplement slurry is evenly coated on the surface of the active layer away from the current collector to obtain a lithium supplement layer; and the electrode sheet is obtained by drying and rolling.
[0153] Preferably, the solid content of the lithium supplementing slurry is 65-85%, and the viscosity is 4000-12000 MPa·S; optionally, the solvent in the lithium supplementing slurry includes N-methyl-2-pyrrolidone (NMP).
[0154] In a third aspect, the present invention provides a battery, comprising the lithium supplement material of the first aspect or the electrode sheet of the second aspect.
[0155] The battery provided by the present invention, because it includes the lithium replenishing material of the first aspect or the electrode sheet of the second aspect, can achieve a good lithium replenishing effect, has high safety performance, and can reduce the internal resistance of the battery.
[0156] Hereinafter, a lithium supplement material provided by the present invention is described in detail through specific embodiments.
[0157] Example 1
[0158] (1) Preparation of lithium supplement materials:
[0159] Take carbon fiber paper of any size and use ethanol, acetone and pure water to ultrasonically clean the carbon fiber paper to remove impurities; after cleaning, place it in a baking oven and dry it at 80°C for 24 hours for use; wherein the carbon fiber in the carbon fiber paper has a diameter of 300nm and a length of 5μm;
[0160] A lithium foil not smaller than the size of the carbon fiber paper is placed in an aluminum composite foil shell, and then the spare carbon fiber paper is closely attached to the lithium foil, and then an electrolyte containing 1.2 mol / L LiTFSi is injected into the closely attached lithium foil and carbon fiber paper in a dry environment, so that the electrolyte completely infiltrates the carbon fiber paper; after the electrolyte is injected, the outer aluminum composite foil shell is sealed for pre-lithiation treatment, that is, the lithium foil is used as the anode and the conductive matrix is used as the cathode, and charging is performed for 120 minutes, the carbon fiber paper is peeled off from the lithium foil, and washed twice with dimethyl carbonate (DMC), and the carbon fiber paper is dried at 25±5°C to obtain a pre-lithiation carbon fiber paper, that is, a lithium supplement material, and the chemical formula of the lithium supplement matrix is Li 0.5 C6, and through SEM testing, it can be seen that A1 / (A1+A2) is 40%.
[0161] (2) Preparation of negative electrode sheet:
[0162] The lithium supplement material is mechanically crushed to a D50 particle size of 10 μm;
[0163] The crushed lithium supplement material, binder (polyvinylidene fluoride), conductive agent (conductive carbon black and carbon nanotubes, mass ratio of 3:1) and solvent (NMP) are mixed and stirred uniformly to obtain negative electrode lithium supplement slurry; wherein the mass ratio of lithium supplement material, binder and conductive agent is 90:6:4, and the solid content of negative electrode lithium supplement slurry is 70% and the viscosity is 8000MPa·S by controlling the amount of solvent added; D50 of conductive carbon black is 3μm;
[0164] like Figure 2 As shown, the negative electrode lithium supplement slurry is evenly coated on the front and back sides of the current collector (copper foil) to obtain a lithium supplement layer; wherein the thickness of the lithium supplement layer is 5 μm and the porosity is 32%;
[0165] The negative electrode active material (including 90wt% of artificial graphite and 10wt% of silicon-carbon material, the mass content of silicon element in the silicon-carbon material is 6%), conductive carbon black, polyacrylic acid (PAA), and sodium carboxymethyl cellulose are placed in deionized water at a mass ratio of 97.2:0.5:1.3:1, and stirred evenly to prepare a negative electrode active material slurry; wherein the D50 of the negative electrode active material is 12μm;
[0166] The negative electrode active material slurry was evenly coated on the surface of the lithium supplement layer away from the current collector to obtain a negative electrode active material layer, which was dried and rolled to obtain a compacted density of 1.72 g / cm 3 The negative electrode sheet has a porosity of 45% in the negative electrode active material layer.
[0167] (3) Preparation of positive electrode sheet:
[0168] Lithium cobalt oxide, conductive agent (a mixture of conductive carbon black and carbon nanotubes, with a mass ratio of 3:1), and PVDF were placed in NMP at a mass ratio of 97.60:1.35:1.05, and stirred evenly to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on the front and back sides of the aluminum foil, and then dried and rolled to obtain a compacted density of 4.15 g / cm 3 The positive electrode.
[0169] Example 2
[0170] The difference between this embodiment and embodiment 1 is that in the step (2) of preparing the negative electrode sheet, the thickness of the lithium supplement layer is 2 μm.
[0171] Example 3
[0172] The difference between this embodiment and embodiment 1 is that in the step (2) of preparing the negative electrode sheet, the thickness of the lithium supplement layer is 15 μm.
[0173] Example 4
[0174] The difference between this embodiment and embodiment 1 is that in the step (2) of preparing the negative electrode sheet, the D50 of the lithium supplement material is 30 μm, and the porosity of the lithium supplement layer is 21%.
[0175] Example 5
[0176] The difference between this embodiment and embodiment 1 is that in the step (2) of preparing the negative electrode sheet, the D50 of the conductive agent is 15 μm, and the porosity of the lithium supplement layer is 27%.
[0177] Example 6
[0178] The difference between this embodiment and embodiment 1 is that in the preparation step (2) of the negative electrode sheet, the mass percentage of silicon in the negative electrode active material is adjusted, specifically, including 80wt% of artificial graphite and 20wt% of silicon-carbon material, and the porosity of the negative electrode active material layer is 43%.
[0179] Example 7
[0180] The difference between this embodiment and embodiment 1 is that in the preparation step (3) of the positive electrode sheet, lithium cobalt oxide is replaced by a mixture of lithium cobalt oxide and a ternary positive electrode material, the mixing mass ratio is 1:1, and the chemical composition of the ternary positive electrode material is Li 1.05 Ni 0.6 Co 0.2 Mn 0.2 O2.
[0181] Example 8
[0182] The difference between this embodiment and embodiment 1 is that in the step (2) of preparing the negative electrode sheet, the porosity of the lithium supplement layer is 12%.
[0183] Example 9
[0184] The difference between this embodiment and embodiment 1 is that in the preparation step (1) of the lithium supplement material, the pre-lithiation treatment time is 10 minutes, and the chemical formula of the lithium-containing matrix in the lithium supplement material is Li 0.2 C6, after SEM testing, it was found that A1 / (A1+A2) was 20%.
[0185] Example 10
[0186] The difference between this embodiment and embodiment 1 is that in the preparation step (1) of the lithium supplement material, the pre-lithiation treatment time is 360 minutes, and the chemical formula of the lithium-containing matrix in the lithium supplement material is Li 0.7 C6, after SEM testing, it was found that A1 / (A1+A2) was 70%.
[0187] Embodiment 11
[0188] The difference between this embodiment and embodiment 1 is that in the step (2) of preparing the negative electrode sheet, the mass ratio of the lithium supplement material, the binder and the conductive agent is 65:20:15, and the porosity of the lithium supplement layer is 35%.
[0189] Example 12
[0190] The difference between this embodiment and embodiment 1 is that: Preparation of negative electrode sheet:
[0191] The pulverized lithium supplement material (D50 particle size is 10 μm), the negative electrode active material (including 90 wt% of artificial graphite and 10 wt% of silicon-carbon material, the mass content of silicon element in the silicon-carbon material is 6%), the conductive agent conductive carbon black (D50 is 3 μm), the binder (polyvinylidene fluoride) and the solvent (NMP) are mixed to obtain a mixed slurry; wherein the mass ratio of the lithium supplement material to the negative electrode active material is 7:93, and the solid content of the lithium supplement slurry is 70% and the viscosity is 8000 MPa·S by controlling the amount of solvent added; wherein the D50 of the negative electrode active material is 12 μm;
[0192] like Figure 6 As shown, the mixed slurry is evenly coated on the front and back sides of the current collector (copper foil) to obtain a mixed layer; wherein the thickness of the mixed layer is 40 μm and the porosity is 32%; and after drying and roller pressing, a compaction density of 1.72 g / cm 3 The negative electrode.
[0193] Embodiment 13
[0194] The difference between this embodiment and embodiment 12 is that in the step (2) of preparing the negative electrode sheet, the D50 of the conductive agent is 15 μm.
[0195] Embodiment 14
[0196] The difference between this embodiment and embodiment 12 is that in the step (2) of preparing the negative electrode sheet, the mass ratio of the lithium supplement material to the negative electrode active material is 2:98.
[0197] Embodiment 15
[0198] The difference between this embodiment and embodiment 1 is that: the negative electrode sheet does not include a lithium supplement layer, the negative electrode active material layer is arranged on the front and back sides of the negative electrode current collector copper foil, and the other parts remain unchanged;
[0199] In the positive electrode sheet, the lithium supplement layer is arranged on the front and back sides of the positive electrode current collector aluminum foil, and the positive electrode slurry is evenly coated on the surface of the lithium supplement layer away from the current collector to obtain the positive electrode active material layer, and the rest remains unchanged.
[0200] Example 16
[0201] The difference between this embodiment and embodiment 1 is that in the step (2) of preparing the negative electrode sheet, the negative electrode active material layer is first coated on the front and back sides of the negative electrode current collector, and then the lithium supplement layer is coated on the two outer surfaces of the negative electrode active material layer to obtain the negative electrode sheet. The other parts are the same as those in embodiment 1. The structure of the negative electrode sheet is as follows Figure 1 shown.
[0202] Embodiment 17
[0203] The difference between this embodiment and embodiment 1 is that in the step (2) of preparing the negative electrode sheet, the negative electrode active material layer is first coated on the front and back sides of the negative electrode current collector, and then the lithium replenishing layer is coated on the two outer surfaces of the negative electrode active material layer, and finally the negative electrode active material layer is coated on the outer surfaces of the two lithium replenishing layers to obtain the negative electrode sheet. The other parts are the same as those in embodiment 1. The structure of the negative electrode sheet is as follows Figure 3 shown.
[0204] Embodiment 18
[0205] The difference between this embodiment and embodiment 1 is that in the step (2) of preparing the negative electrode sheet, the negative electrode active material layer is first coated on both the front and back sides of the negative electrode current collector, and then the lithium supplement layer is coated on any outer surface of the negative electrode active material layer to obtain the negative electrode sheet. The other aspects are the same as those of embodiment 1. The structure of the negative electrode sheet is as follows Figure 4 shown.
[0206] Embodiment 19
[0207] The difference between this embodiment and embodiment 1 is that in the step (2) of preparing the negative electrode sheet, a lithium supplement layer is firstly coated on any outer surface of the negative electrode current collector, and then a negative electrode active material layer is coated on the outer surface of the lithium supplement layer and the other outer surface of the negative electrode current collector to obtain a negative electrode sheet. The other aspects are the same as those of embodiment 1. The structure of the negative electrode sheet is as follows Figure 5 shown.
[0208] Embodiment 20
[0209] The difference between this embodiment and embodiment 12 is that: negative electrode active material layers are coated on both surfaces of the mixed layer, and the composition of the negative electrode active material layers is consistent with that of embodiment 1; wherein the thickness of the mixed layer is 15 μm, and the thickness of the negative electrode active layer is 25 μm, to obtain a negative electrode sheet, and the rest is consistent with that of embodiment 12. The structure of the negative electrode sheet is as follows Figure 7 shown.
[0210] Embodiment 21
[0211] The difference between this embodiment and embodiment 1 is that: a negative electrode active material layer is coated on the two outer surfaces of the negative electrode current collector, and then a mixed layer is coated on the two outer surfaces of the negative electrode active material layer respectively, and the composition of the mixed layer is consistent with that of embodiment 12 to obtain a negative electrode sheet, and the rest is consistent with that of embodiment 1. The structure of the negative electrode sheet is as follows Figure 8 shown.
[0212] Embodiment 22
[0213] The difference between this embodiment and embodiment 15 is that the positive electrode active material layer is first coated on the front and back sides of the positive electrode current collector, and then the lithium supplement layer is coated on the two outer surfaces of the positive electrode active material layer to obtain a positive electrode sheet. The rest is the same as embodiment 15. The structure of the positive electrode sheet is as follows Figure 1 shown.
[0214] Embodiment 23
[0215] The difference between this embodiment and embodiment 15 is that: firstly, a positive electrode active material layer is coated on both sides of the positive electrode current collector, then a lithium replenishing layer is coated on the two outer surfaces of the positive electrode active material layer, and finally, a positive electrode active material layer is coated on the outer surfaces of the two lithium replenishing layers to obtain a positive electrode sheet, and the rest is the same as embodiment 15. The structure of the positive electrode sheet is as follows Figure 3 shown.
[0216] Embodiment 24
[0217] The difference between this embodiment and embodiment 15 is that: the positive electrode active material layer is first coated on the front and back sides of the positive electrode current collector, and then the lithium supplement layer is coated on any outer surface of the positive electrode active material layer to obtain a positive electrode sheet. The rest is the same as embodiment 15. The structure of the positive electrode sheet is as follows Figure 4 shown.
[0218] Embodiment 25
[0219] The difference between this embodiment and embodiment 15 is that: a lithium supplement layer is firstly coated on any outer surface of the positive electrode current collector, and then a positive electrode active material layer is coated on the outer surface of the lithium supplement layer and the other outer surface of the positive electrode current collector to obtain a positive electrode sheet, and the rest is the same as embodiment 15. The structure of the positive electrode sheet is as follows Figure 5 shown.
[0220] Embodiment 26
[0221] The difference between this embodiment and embodiment 15 is: Preparation of the positive electrode sheet:
[0222] The crushed lithium supplement material (D50 particle size is 10 μm), lithium cobalt oxide, conductive agent (a mixture of conductive carbon black and carbon nanotubes, mass ratio is 3:1), and PVDF are placed in NMP; wherein the mass ratio of the lithium supplement material to the positive electrode active material is 7:93, and stirred evenly to obtain a mixed slurry; the mixed slurry is evenly coated on the front and back sides of the aluminum foil, and then dried and rolled to obtain a compacted density of 4.15 g / cm 3 The positive electrode sheet is the same as that of Example 15. The structure of the positive electrode sheet is as follows Figure 6 shown.
[0223] Embodiment 27
[0224] The difference between this embodiment and embodiment 26 is that the positive electrode active material layer is coated on the two outer surfaces of the mixed layer to obtain a positive electrode sheet, and the rest is the same as that of embodiment 26. The structure of the positive electrode sheet is as follows Figure 7 shown.
[0225] Embodiment 28
[0226] The difference between this embodiment and embodiment 26 is that the positive electrode active material layer is coated on the two outer surfaces of the positive electrode current collector respectively, and then the mixed layer is coated on the two outer surfaces of the positive electrode active material layer to obtain a positive electrode sheet, and the rest is the same as embodiment 26. The structure of the positive electrode sheet is as follows Figure 8 shown.
[0227] Embodiment 29
[0228] The difference between this embodiment and embodiment 1 is that in the preparation of the lithium supplement material, the carbon fiber paper is replaced by graphite fiber, and the diameter of the graphite fiber is 200 nm and the length is 10 μm.
[0229] Embodiment 30
[0230] The difference between this embodiment and embodiment 1 is that in the preparation of the lithium supplement material, the fiber diameter in the carbon fiber paper is 10 nm and the length is 1 μm.
[0231] Embodiment 31
[0232] The difference between this embodiment and embodiment 1 is that in the preparation of the lithium supplement material, the fiber diameter in the carbon fiber paper is 500 nm and the length is 20 μm.
[0233] Comparative Example 1
[0234] The difference between this comparative example and Example 1 is that: no lithium supplement layer is provided on the negative electrode, and the negative electrode active material slurry is directly coated on the front and back surfaces of the negative electrode current collector.
[0235] Comparative Example 2
[0236] The difference between this comparative example and Example 1 is that the preparation of the lithium supplement material comprises the following steps:
[0237] (1) Graphene is mixed with a solvent to form a slurry; the slurry is formed into a film on a substrate, and then treated at 60°C to 180°C for 1 min to 2 h, and then the substrate is removed, and the film is treated at 180°C to 1000°C in an inert atmosphere for 0.5 h to 10 h, and then cooled to room temperature; in a dry atmosphere, the film is pressed into a conductive carbon film; wherein the conductive carbon film has a thickness of 10 μm and a density of 1.5 g / cm 3 ~2.2g / cm 3 , resistivity <0.01Ω·cm;
[0238] (2) in an inert atmosphere, immersing the dried conductive carbon film in a molten lithium metal solution at 300° C. to 500° C., maintaining the solution for 1 second to 500 seconds, then transferring the conductive carbon film to a molten lithium metal solution at 180° C. to 300° C., maintaining the solution for 1 second to 500 seconds, and then taking the film out;
[0239] (3) Scraping the surface of the membrane obtained in step (2) to control the thickness of the lithium metal layer to be 1 μm to 300 μm; obtaining a lithium carbon compound at the interface between the conductive carbon film and the lithium metal layer, namely, a lithium supplement material.
[0240] Comparative Example 3
[0241] The difference between this comparative example and Example 1 is that the lithium supplement material is Li2C2O4.
[0242] Comparative Example 4
[0243] The difference between this comparative example and Example 1 is that in the preparation step (2) of the lithium supplement material, the pre-lithiation treatment time is 480 min, and the chemical formula of the lithium supplement material is Li 0.9 C6, after SEM testing, it was found that A1 / (A1+A2) was 90%.
[0244] Comparative Example 5
[0245] The difference between this comparative example and Example 1 is that in the preparation step (2) of the lithium supplement material, the pre-lithiation treatment time is 3 minutes, and the chemical formula of the lithium supplement material is Li 0.1 C6, after SEM testing, it was found that A1 / (A1+A2) was 10%.
[0246] Comparative Example 6
[0247] The difference between this comparative example and Example 1 is that in the step (1) of preparing the lithium supplement material, the carbon fiber in the carbon fiber paper has a diameter of 800 nm and a length of 20 μm.
[0248] Test Example 1
[0249] Preparation of the battery:
[0250] The diaphragm is 9 μm thick; the electrolyte includes lithium salt (LiPF6) and a solvent, the solvent includes ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC), wherein the molar ratio of DEC, EC and EMC is 1:1:1, and the added lithium salt accounts for 12% of the total mass of the solvent; the positive electrode sheets, diaphragms and negative electrode sheets cut in the above embodiments and comparative examples are stacked in sequence and wound into a wound structure battery cell, the battery cell is packaged, injected with liquid, and left to stand, and then the first charge and discharge test is carried out.
[0251] The test conditions are: standing for 5 minutes; charging at 0.1C for 30 minutes, with a cut-off voltage of 3.7V; after standing for 5 minutes, charging at 0.5C for 6 minutes with a cut-off voltage of 4.0V; standing for 1 minute, charging at 1C for 40 minutes, with a cut-off voltage of 4.5V, at this time the charging capacity is recorded as Q1; then standing for 5 minutes, charging at 0.5C to 4.5V with a cut-off current of 0.05C, at this time the charging capacity is recorded as Q2; then discharging at 0.2C to 3.0V, at this time the discharge capacity is recorded as q; first coulomb efficiency (%) = q / (Q1+Q2)×100%.
[0252] Under 50% SOC conditions, the internal resistance of the battery was measured by AC impedance test.
[0253] The capacity retention rate and expansion rate of each battery obtained were tested, and the specific test method was as follows: before the test, the thickness H0 of the fully charged battery cell was tested; at 25°C, the battery was charged to 4.3V at a constant current of 3.2C with a cut-off current of 2.5C, and then charged to 4.4V at a constant current of 2.5C with a charge rate, and then charged to 4.5V at a constant current of 1.5C with a cut-off current of 0.2C; then the battery was discharged to 3V at a discharge rate of 0.7C; the battery was cycled according to the aforementioned charge and discharge mechanism for 400 cycles, and then the battery was fully charged, the battery cell was taken out, and it was left to stand at room temperature for 1 hour, and the thickness H1 when fully charged was tested; then the battery was connected continuously and the number of cycles when the capacity was less than 80% was recorded.
[0254] The expansion rate after 400 cycles is calculated according to the following formula:
[0255] Expansion rate (%) = (H1-H0) / H0*100%
[0256] The above test results are shown in Table 1.
[0257] Table 1
[0258]
[0259]
[0260]
[0261] From Table 1, we can see that:
[0262] The lithium ion batteries in Examples 1 to 31 have higher capacity, first coulomb efficiency and cycle performance than those in Comparative Examples 1 to 6, and also have lower expansion rate; wherein, the first coulomb efficiency of the lithium ion battery in Example 1 is as high as 87.56%, correspondingly, the number of cycles when the capacity is less than 80% is 694T, and the expansion rate is only 10.09% when the cycle is 500T, and the capacity is also relatively high, which is 4938.54mAh; the performance of the battery is significantly higher than that of Comparative Examples 1 to 6. It can be seen that the lithium supplement material of the present invention can effectively solve the problems of high chemical activity and poor safety of lithium supplement materials in the prior art, which easily lead to increased battery expansion rate, increased internal resistance, and poor lithium supplement effect.
[0263] Test Example 2
[0264] The negative electrode sheets prepared in the above embodiments and comparative examples were tested to obtain the thickness D1 of the lithium replenishing layer and the thickness D of the negative electrode active material layer; a lithium ion battery without a lithium replenishing layer (the only difference from the lithium ion battery prepared above is that the negative electrode sheet does not contain a lithium replenishing layer, and the other aspects are the same) was charged to 4.5V at 0.5C for the first time, charged at a constant voltage to 0.05C and then stopped, and after standing for 3 minutes, the lithium ion battery was disassembled to measure the thickness D2 of the negative electrode active material layer without a lithium replenishing layer after full charge, and the value of (D2-D) / D1 was measured and calculated.
[0265] Each battery obtained was discharged to 3V at 0.5C for the first time and allowed to stand for 3 minutes. The battery was then disassembled to measure the porosity ε2 of the active material layer and the porosity ε1 of the lithium supplement layer. The value of ε1 / ε2 was calculated.
[0266] The above test results are shown in Table 2.
[0267] Table 2
[0268]
[0269]
[0270] From Table 2, we can see that:
[0271] The lithium supplement material provided by the present invention includes a conductive matrix and a lithium-containing matrix embedded in at least a part of the conductive matrix. The conductive matrix has good conductivity and can easily form a good conductive network in the electrode, which can reduce electrode polarization, reduce battery internal resistance and improve battery performance; and the lithium supplement material can alleviate the expansion of the negative electrode active material. When lithium ions are consumed, a thickness space is reserved to alleviate the expansion of the negative electrode sheet; and the lithium supplement material can accommodate more electrolyte, thereby improving the battery cycle life and cycle performance. In summary, the lithium supplement material provided by the present invention can take into account both improving the lithium supplement effect and safety performance, and at the same time can reduce the battery internal resistance.
[0272] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lithium supplement material, characterized in that: The lithium supplement material includes a conductive matrix and a lithium-containing matrix embedded in at least a portion of the conductive matrix; The conductive matrix includes carbon fibers and / or graphite fibers; The chemical formula of the lithium-containing matrix is Li x C6, where 0.2≤x≤0.7; The carbon fiber and / or the graphite fiber has a diameter of 2 to 500 nm and a length of 1 to 20 μm.
2. The lithium supplement material according to claim 1, characterized in that: The lithium supplement material includes a lithium insertion region and a non-lithium insertion region, and the lithium supplement material satisfies: 20%≤A1 / (A1+A2)×100%≤70%, wherein A1 is the area of the lithium insertion region, and A2 is the area of the non-lithium insertion region.
3. An electrode sheet, characterized in that: The electrode sheet comprises a current collector and a functional layer disposed on at least a portion of the surface of the current collector, wherein the functional layer comprises the lithium supplement material according to claim 1 or 2.
4. The electrode sheet according to claim 3, characterized in that: The functional layer comprises a lithium replenishing layer and an active material layer which are stacked, the lithium replenishing layer comprises the lithium replenishing material, and the active material layer comprises an active material; or, The functional layer includes a mixed layer, and the mixed layer includes an active material and the lithium supplement material; or, The functional layer includes an active material layer and a mixed layer which are stacked, the active material layer includes an active material, and the mixed layer includes an active material and the lithium supplementing material.
5. The electrode sheet according to claim 4, characterized in that: The electrode sheet is a positive electrode sheet, in which the active material layer is a positive electrode active material layer, and the active material is a positive electrode active material; or, the electrode sheet is a negative electrode sheet, in which the active material layer is a negative electrode active material layer, and the active material is a negative electrode active material; Wherein, the active material layer and the lithium supplement layer are sequentially arranged on the two surfaces of the current collector respectively; or, The lithium replenishing layer and the active material layer are sequentially arranged on two surfaces of the current collector respectively; or, The active material layer includes a first active material layer and a second active material layer, and the first active material layer, the lithium replenishing layer and the second active material layer are sequentially arranged on two surfaces of the current collector respectively; or, The active material layer is disposed on any one surface of the current collector, and the active material layer and the lithium supplement layer are sequentially disposed on the other surface; or, The active material layer is disposed on any one surface of the current collector, and the lithium replenishing layer and the active material layer are sequentially disposed on the other surface; or, The mixed layer is disposed on both surfaces of the current collector; or, The mixed layer and the active material layer are sequentially disposed on both surfaces of the current collector; or, The active material layer and the mixed layer are sequentially disposed on both surfaces of the current collector.
6. The electrode sheet according to claim 5, characterized in that: In the negative electrode sheet, the negative electrode active material includes a silicon-based material, and the mass percentage of the silicon-based material in the negative electrode active material layer is 0 to 50%; or, In the positive electrode sheet, the positive electrode active material includes a metal oxide represented by Formula 1 and / or Formula 2; Li a1 Co x1 A 1 k1 O2 type 1Li a2 Ni x2 Co y2 D z2 A 2 k2 O2 Formula 2 In the formula, 0.85≤al≤1.1, 0.85≤a2≤1.1, 0.3≤x1≤0.9, 0.3 <x2≤0.9,0≤y2≤0.5,0.1≤z2≤0.5,0≤kl≤0.15,0≤k2≤0.15; D includes at least one of Mn or Al; A 1 and A 2 Each independently includes at least one of Al, Mg, Ti, Zr, Y, La, W, B, Nb and Mn.
7. The electrode sheet according to any one of claims 4 to 6, characterized in that: In the mixed layer, the mass ratio of the lithium supplementing material to the active material is (5-10):(90-95).
8. The electrode sheet according to any one of claims 4 to 7, characterized in that: The porosity of the lithium supplement layer satisfies Formula 3: ε1=(0.4~1)ε2 Formula 3 In Formula 3, ε1 is the porosity of the lithium supplement layer, in %; ε2 is the porosity of the active material layer, in %.
9. The electrode sheet according to claim 8, characterized in that: The porosity ε1 of the lithium supplement layer is 16-35%, and / or the porosity ε2 of the active material layer is 20-45%.
10. The electrode sheet according to any one of claims 4 to 9, characterized in that: The electrode sheet is a negative electrode sheet, and the lithium supplement layer further includes a binder and a conductive agent; wherein the mass ratio of the lithium supplement material, the binder and the conductive agent is (80-98): (1-10): (1-10); Or, the electrode sheet is a positive electrode sheet, and the lithium supplement layer further includes an inorganic substance and a conductive agent; wherein the mass ratio of the lithium supplement material, the inorganic substance and the conductive agent is (10-40): (55-90): (0-5); Preferably, the conductive agent includes at least one of conductive carbon black, conductive graphite, carbon fiber, carbon nanotube, and graphene; Preferably, the inorganic substance includes at least one of boehmite, alumina, silicon dioxide and lithium iron phosphate.
11. A battery, characterized in that: It includes the lithium supplement material according to claim 1 or 2 or the electrode sheet according to any one of claims 3-10.
Citation Information
Patent Citations
Lithium supplement modification method for lithium ion positive electrode material
CN112038638A
Positive lithium supplementing pole piece, preparation method thereof and lithium ion battery
CN115939391A
Negative plate and battery
CN117352649A
Electrode, secondary battery, and electric device
CN118231564A
Lithium supplement negative plate and lithium ion battery
CN118315531A
Cited By
Lithium supplementing composite layer and preparation method thereof, lithium supplementing method, pre-lithiated negative pole piece, secondary battery and electronic device
CN119920903A